Effects of an intervention on emotional and cognitive engagement in teacher education: scientific practices concerning greenhouse gases - López-Banet, Luisa; Martínez-Carmona, Marina; Reis, Pedro (Frontiers in Education, 2024)
Recent studies advise teachers of the need to become aware of the importance of linking the cognitive and affective in learning. During initial training, teaching approaches linked to scientific practices of inquiry and modeling can increase the emotions experienced in the teaching–learning process and encourage teachers to reflect and be aware of how they learn. This research focused on considering that scientific practices should include the environmental problems that society faces today. Thus, activities were contextualized with a theme of economic, scientific and environmental repercussions. Moreover, it promoted awareness about the important role that different scientists have played in the advancement of knowledge about the greenhouse effect and its consequences. The main objective of this research was to allow trainee teachers to become conscious of how they learn content and their relationship with the emotions experienced. The instructional sequence consisted of a set of activities (inquiry, modeling, argumentation), based on the effects of certain chemical substances responsible for the greenhouse effect, focused on promoting the active participation of students. After completion of the instructional sequence, perceptions of pre-service teachers concerning their own learning after the instruction were analyzed. The results evidenced that self-perception of learning and emotions were directly correlated. The emotions experienced during the training appeared to influence the perceptions of the activities and, consequently, their perspectives when deciding whether or not to implement such activities in the future.